Limited Short-Term Impact of Annual Cover Crops on Soil Carbon and Soil Enzyme Activity in Subtropical Tree Crop Systems - Abraham J. Gibson; Lee J. Kearney; Karina Griffin; Michael T. Rose; Terry J. Rose (Agronomy, 2025)
In wet subtropical environments, perennial groundcovers are common in horticultural plantations to protect the soil from erosion. However, there has been little investigation into whether seeding annual cover crops into the perennial groundcovers provides additional soil services including carbon and nutrient cycling in these systems. To investigate this, farmer participatory field trials were conducted in commercial avocado, macadamia, and coffee plantations in the wet Australian subtropics. Cover crops were direct-seeded into existing inter-row groundcovers in winter (cool season cover crops), and into the same plots the following summer (warm season cover crops). Inter-row biomass was quantified at the end of winter and summer in the control (no cover crop) and cover crops treatments. Soil carbon and nutrient cycling parameters including hot water extractable carbon, water soluble carbon, autoclavable citrate-extractable protein and soil enzyme activities were quantified every two months from early spring (September) 2021 to late autumn (May) 2022. Seeded cover crops produced 500 to 800 kg ha−1 more total inter-row biomass over winter at the avocado coffee sites, and 3000 kg ha−1 biomass in summer at the coffee site. However, they had no effect on biomass production in either season at the macadamia site. Soil functional parameters changed with season (i.e., time of sampling), with few significant effects of cover crop treatments on soil function parameters across the three sits. Growing a highly productive annual summer cover crop at the coffee site led to suppression and death of perennial groundcovers, exposing bare soil in the inter-row by 3 weeks after termination of the summer cover crop. Annual cover crops seeded into existing perennial groundcovers in tree crop systems had few significant impacts on soil biological function over the 12-month period, and their integration needs careful management to avoid investment losses and exacerbating the risk of soil erosion on sloping lands in the wet subtropics.